THE INFLUENCE OF LANGUAGE COMPETENCE, WRITING COMPETENCE, AND CULTURAL COMPETENCE ON PRODUCING A SUCCESSFUL WRITING - Hermanto (Jurnal Sosial Humaniora, 2025)
Writing is a skill derived from a long way of learning and exercises. Different from other language skills, writing is considered the difficult language skill to acquire since it involves many aspects of linguistics, social, and writing knowledge and conventions. There are at least three important elements of writing useful to produce a good piece of composition, language competence, writing competence and cultural competence. This paper shows the influence of these three elements in order to produce good, readable, communicative, and successful writing.